2015
DOI: 10.3166/rfg.251.115-130
|View full text |Cite
|
Sign up to set email alerts
|

De l’intuition dans la décision des managers de l’action publique

Abstract: De l'intuition dans la décision des managers de l'action publique Le cas du pilotage des réseaux territorialisés d'organisations 1. Avec le soutien financier de la Direction générale de l'armement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Indeed, the literature has shown that certain types of intuitions are not accessible to novices. We therefore included in our sample respondents with recognised expertise in their field (Dane & Pratt, 2007), whom we identified on the basis of the length of their professional experience (Glöckner & Witteman, 2010), their hierarchical level (Bertolucci & Pinzon, 2015) and the recommendations of their peers (Kahneman & Klein, 2009). Furthermore, we decided to interview middle managers in organisations with at least 50 members in order to maximise the chances of identifying legitimation episodes, because middle managers are often confronted with complex situations and have to legitimate their intuitions to their superiors, their peers or their subordinates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the literature has shown that certain types of intuitions are not accessible to novices. We therefore included in our sample respondents with recognised expertise in their field (Dane & Pratt, 2007), whom we identified on the basis of the length of their professional experience (Glöckner & Witteman, 2010), their hierarchical level (Bertolucci & Pinzon, 2015) and the recommendations of their peers (Kahneman & Klein, 2009). Furthermore, we decided to interview middle managers in organisations with at least 50 members in order to maximise the chances of identifying legitimation episodes, because middle managers are often confronted with complex situations and have to legitimate their intuitions to their superiors, their peers or their subordinates.…”
Section: Methodsmentioning
confidence: 99%
“…To managers, rationality appears to be self-evident, as much because it is performative (Cabantous & Gond, 2011) as because this mental model is implicit in current management education (Czarniawska, 2003). In this light, intuitions naturally appear dubious (Bertolucci & Pinzon, 2015) *Corresponding author: Isabelle Bouty, Email: isabelle.bouty@dauphine.psl.eu Business Voice…”
mentioning
confidence: 99%